A web based houseplants recommender system to optimize residential green initiatives / Nur Syuhada Suhaini - Suhaini, Nur Syuhada (2020)
One of the easiest ways to participate in green initiatives is by planting plants around the house. Nevertheless, this is often overlooked by community of residents of residential areas because of lack of knowledge in choosing houseplants. Therefore, in this study, a web-based Houseplants Recommender System is developed. Houseplants Recommender System could give recommendation of the most suitable houseplants to the user. There are five questions regarding user preference that needs to be answered in order to receive recommendation from the system. The questions surround whether user loves indoor or outdoor plants, high maintenance or low maintenance plants, tropical plants of flowering plants, colourful plants or greenery plants, as well as size of plants whether small or large. In the output user will get information such as common name, scientific name, height, spread, light needed, watering frequency and some of the plant’s essential facts. Houseplants Recommender System techniques of rule bases to recommend houseplants to the user. There are several benefits in using Houseplants Recommender System; which are user can save more time from going to the nursery in order to search and decide on the ideal plant, user can choose the plants several times and get more information about the houseplants before actually deciding to buy it and the system helps user in learning how to care for houseplants properly. Two testing which are Heuristic Evaluation for experts review and User Acceptance Test based on Technology Acceptance Model (TAM) for the end-user were conducted. As a result, most of the respondents agreed Houseplants Recommender System that manage to recommend suitable houseplants based on user preference. Besides that it also provides tips how to take care for indoor plants, how to take care for orchid, how to water plants and types of plants disease.